La représentation des paysages de décharges publiques urbaines au Liban - Nada Chbat (Projets de Paysage)
To analyze the landscapes of the urban discharges is practically to study two main factors : firstly, the geographical factor that takes into consideration the geographical data provided by the site and, secondly, the social factor and the aesthetic and economic values. The urban discharges in Lebanon marked the landscape of the cities where they strongly proliferated since the first years of the war in 1970. They contributed to divide the space and to draw separation lines that didn’t exist between the different districts. They deeply affected the quality of life of the inhabitants while modifying (rupture) what was "their territory" and the representations of their imaginary local. The existence of the discharges and the places to empty trash bins (as the case of the two discharges studied in this article : Borj Hammoud - Beirut - and of Kayyal - Baalbek) contributed to draw some borders between the "zones of discharges" and those on their edge.